1997
DOI: 10.1002/(sici)1098-2736(199708)34:6<551::aid-tea2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of explicit problem solving instruction on high school students' problem-solving performance and conceptual understanding of physics

Abstract: In this study a two-sample, pre/posttest, quasi-experimental design was used to investigate the effect of explicit problem-solving instruction on high school students' conceptual understanding of physics. Eight physics classes, with a total of 145 students, were randomly assigned to either a treatment or comparison group. The four treatment classes were taught how to use an explicit problem-solving strategy, while the four comparison classes were taught how to use a textbook problem-solving strategy. Students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 19 publications
1
45
0
6
Order By: Relevance
“…While the strategies summarised above were all employed at universities, Huffman (1997) explored structured problem solving in high school physics. Huffman demonstrated that an explicit problem solving strategy improved problem solving performance as well as conceptual understanding.…”
Section: Literature Surveysupporting
confidence: 66%
See 2 more Smart Citations
“…While the strategies summarised above were all employed at universities, Huffman (1997) explored structured problem solving in high school physics. Huffman demonstrated that an explicit problem solving strategy improved problem solving performance as well as conceptual understanding.…”
Section: Literature Surveysupporting
confidence: 66%
“…Students were encouraged to substitute numerical values before starting algebraic manipulation, the reason being that poor mathematical abilities could prevent many students from arriving at correct symbolic solutions. Here the current approach differed from others who preferred symbolic solutions before substitution (Huffman, 1997;Wright & Williams, 1986;Reif et al, 1976). It was argued that emphasis on symbolic solutions could be counterproductive for disadvantaged students with poor mathematical skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this study using force concept test and problem-solving strategy rubric as a measurement tool, the students in the experimental group made progress in the visualization step of problem solving strategies. However, in the steps of establishing equality, using formulas, mathematical processing skills, there was no difference in the ability of using use problem solving strategies of the experimental and control group students (Huffman, 1997).…”
Section: Studies On Problem Solving In Physics Educationmentioning
confidence: 99%
“…However, both are designed in a context outside of problem solving and with no mathematics. One high school study [29] did compare the impact of "explicit problem solving instruction" to traditional problem solving instruction on various conceptual and problem solving measures. Both approaches included five steps:…”
Section: Introductionmentioning
confidence: 99%